Diagnostic Value and Application of Infrared Thermography in the Analysis of Circumanal Gland Tumors - Zanuto, Erika B. M.; Melo, Samanta R.; Januário, Eric V.; Fernandes, Gustavo A. A. L.; Matera, Julia M. (Frontiers in Veterinary Science, 2021)
In dogs, circumanal tumors are the third most common skin neoplasm. Circumanal gland adenomas (CAGAs) have a good prognosis. Contrastingly, circumanal gland adenocarcinomas (CAGAC) have high relapse rates and may be metastatic. This study aimed to investigate the utility of thermal imaging as an ancillary modality for the diagnosis of canine CAGA and CAGAC. We analyzed the following parameters: SpT, temperature measured at the tumor center; SpNT, temperature measured at a healthy sphincter skin spot distant from the tumor; TA, temperature measured at a tumor-encompassing ellipse-shaped area; and NTA, temperature measured at an ellipse-shaped area of the healthy sphincter skin distant from the tumor. In CAGAs, the mean SpT and SpNT temperature values differed by −1.45°C (p < 0.01) while the mean TA and NTA temperature values differed by −0.96°C (p < 0.05). In CAGACs, mean SpT and SpNT temperatures differed by −1.71°C (p < 0.01) while the mean TA and NTA temperatures differed by −1.69°C (p < 0.01). The mean SpT and TA temperature values measured in CAGAs and CAGACs differed by −0.10°C (p = 0.87) and 0.52°C (p = 0.38), respectively. Both tumors were colder than healthy sphincter skin. However, a substantial number of CAGACs were colder than CAGAs. Temperature differences ≥ 1°C between tumors and healthy sphincter skin increased the probability of CAGAC diagnosis by 17.45%. Thermal imaging allowed discrimination between healthy and tumoral tissues; therefore, it could be a good ancillary diagnostic modality.